Third of patients have gustatory dysfunction 9 months after SARS-CoV-2 infection: the ANOSVID study. (June 2022) - Klopfenstein, Timothée; Tipirdamaz, Can; Gendrin, Vincent; Osman, Molka; Mercier, Julien; Bouvier, Elodie; Bouiller, Kevin; Lepiller, Quentin; Toko, Lynda; Pierron, Alix; Royer, Pierre-Yves; Garnier, Pauline; et al.
Highlights: Nine months after COVID-19 GD, hypogeusia is present in 30% of cases. However, ageusia is scarce. Patients with GD persistence have more frequently recurrences than continuous GD. A long duration of GD and cacosmia could be predictive factors of GD persistence.